2022
DOI: 10.1590/1806-9304202200030003
|View full text |Cite
|
Sign up to set email alerts
|

Association between ultra-processed food consumption and nutrient intake among low-risk pregnant women

Abstract: Objectives: to analyze the ultra-processed foods (UPF) consumption in pregnant women’s diets associated with nutrient intake. Methods: a cross-sectional study using socioeconomic, anthropometric and food consumption data from low-risk pregnant women. Consumption of energy, macro and micronutrient were obtained through two 24-hour recalls (R24h). The UPF were identified using the NOVA classification, and the percentage of energy from this food was classified in quartiles and associated with nutrient intake. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(38 reference statements)
1
0
0
Order By: Relevance
“…Another interesting finding was an inverse association between greater UPF intake and nutrient intake such as iron, magnesium, potassium, copper, zinc, selenium, and folate. Our findings are corroborated by several previous studies who had demonstrated the association between UPF intake and lower dietary fiber, vitamins, and minerals daily consumption, showing that UPFs negatively impact the quality of the diet [38][39][40]47]. The negative impact of UPFs on nutrient content in pregnant women observed in this study is of critical concern as pregnancy is a period when nutritional requirements are markedly increased [3].…”
Section: Discussionsupporting
confidence: 90%
“…Another interesting finding was an inverse association between greater UPF intake and nutrient intake such as iron, magnesium, potassium, copper, zinc, selenium, and folate. Our findings are corroborated by several previous studies who had demonstrated the association between UPF intake and lower dietary fiber, vitamins, and minerals daily consumption, showing that UPFs negatively impact the quality of the diet [38][39][40]47]. The negative impact of UPFs on nutrient content in pregnant women observed in this study is of critical concern as pregnancy is a period when nutritional requirements are markedly increased [3].…”
Section: Discussionsupporting
confidence: 90%
“…Malta et al (2021) também comprova que uma intervenção precoce reduz o risco de uma alimentação inadequada, tendo por base o seu estudo onde houve uma intervenção menor do que o esperado dado que a intervenção 41 Enfermagem Materna e Obstétrica: cuidar na gravidez -ISBN 978-65-5360-374-5 -Vol. 1 -Ano 2023 -Editora Científica Digital -www.editoracientifica.com.br a nível nutricional deu-se numa fase pré-concecional explicado com o facto de ser mais fácil remover alimentos discriminatórios do que introduzir alimentos saudáveis.A gravidez é um período de várias alterações emocionais, sociais e fisiológicas, pelo que é importante a qualidade da alimentação da grávida, pois más escolhas nutricionais podem comprometer a evolução da gravidez tal como comprovamSilva et al (2022) no seu estudo afirmando que uma alimentação com base em alimentos ultraprocessados está associado a um maior risco de diabetes gestacional, pré-eclampsia e/ou ganho/manutenção de peso pós-parto. A gravidez é, portanto, um momento oportuno para o desenvolvimento de ações com o objetivo de promover uma alimentação saudável, tal como afirma Becker et al(2020) comprovando no seu estudo que a gravidez é um período que a mulher idealiza uma alimentação saudável e passa a selecionar melhor os alimentos que consome.…”
unclassified